AI-Driven Transformations in Nursing Preparing the Workforce for Future Healthcare Challenges: Highlights Through Systematic Review - Khalid Mohammed Mohammed Qahtani, Roaa Mosa Mohammed Bakkar, Ibrahem Ahmed Mohammed Meshni, Jmaleeh Alqahtani, Yahya Ahmed Mohammed Siddiq; Zahra Yahia Taher, Ameera Ahmad Alfaqih, Majedah Awad Alruwaili, Intisar Mahmoud Fagihi, Aliah Ali Alghamdi, Samira Yahia Taher (Journal of International Crisis and Risk Communication Research, 2024)
Background: Application of AI in the healthcare sector has been on the increase with great potential for revolutionizing health systems in clinical practice, nursing and workforce. AI is expected to advance the quality of treatment, further the healthcare system configuring, and generate new professions in healthcare, at the same time, controversies linked with the ethical use of AI in healthcare, data protection, and concerns with job lessening continuing to be topical. Aim: Understanding the effectiveness of the nursing workforce, its influence on education, ethics and leadership in a field, general tendencies for AI’s incorporation, potential benefits and issues connected to the application of AI. Method: These ten research studies were chosen to carry out a systematic review that would give a general overview of the current state of AI in healthcare. The selected studies include the following themes: the healthcare workforce, ethical issues, nursing education, and leadership in regards to AI integration. The following data was sought to determine trends and patterns in the use of AI in delivery of health services. Results: AI is opening up new healthcare positions for instance artificial organ specialists while at the same time increasing the efficiency of nurses through such techniques as predictive analytics and robots. However, privacy issues, issues with the algorithms themselves and with the implication of turning healthcare aides into dumb clerks are frequently raised. Conclusion: In respect to the role of AI, the information demonstrates that its application holds numerous benefits for enhancing the delivery of care, management of staff and patients. However there is a need to integrate this to main stream health care delivery systems, but this shouldn’t be done without drawing strong ethical guidelines to govern this new sector, and also without proper training of the healthcare givers on how to deal with these artificial intelligence systems. More work has to be done to overcome those deficits that AI is presented with such as biases, data security, and strong leadership in healthcare organizations.